Remark on digital accessibility: educational disparities define digital inclusion from adolescence onwards - Kaarakainen Meri-Tuulia; Saikkonen Loretta (Springer, 2022)
Along with the digitalisation of societies and services, the accessibility of digital content has become the focus of attention. However, emphasis has been on technical accessibility, ignoring the large number of people suffering from cognitive challenges that are expected to increase as the population ages. The purpose of this study is to demonstrate that the problem affects not only the elderly but also the young. Utilising multivariate methods and a data set of 14,892 young Finns, the study examines the impact of educational disparities on young people’s digital usage and skills. It is observed that the level of education, the form of education and the regularity of the education path are related to differences in digital abilities of young people. Based on the results, the risks of being excluded from digital inclusion accumulate among adolescents for the youngest, but especially for those with a wide range of language, learning or motivational difficulties that manifest as delays in education path. As is known from previous research, such differences are expected to be reinforced in later life, threatening to become rather determinative.